VECTOR SPACE MODEL (VSM) FOR THE SEARCH OF QUR’AN AND HADITHS VERSES ON SCIENCE AND TECHNOLOGY - Taufik, Ichsan; Jaenudin, Mohamad; Badriyah, Fatimah Ulwiyatul; Subaeki, Beki (Institute of Advanced Engineering and Science, 2020)
In Indonesia, there are mobile applications and websites that provide search features in the Qur'an and Hadith, but the search process is still limited to word matching methods, so the system often cannot return relevant information when keywords or keywords are in the form of phrases or sentence. At present there is no website that specifically provides a collection of verses from the Qur'an and Hadith relating to Science and Technology. Therefore, a website-based search application was made that applies the Vector Space Model (VSM) algorithm to search verses and hadith about Science and Technology using the discussion as its parameters. Keywords can be words, phrases or sentences. The results of the percentage of application success using 20 keyword samples, amounting to 81% with an average time of 2.24 seconds.